Hydrometaliurgical Process For Recycling Of Spent Nickel-Metal Hydride Secondary Battery (Invited) - Toshihiro Kuzuya (The Minerals, Metals and Materials Society, 2003)
A hydro metallurgical process has been developed for the recovery of metal values such as Co, Ni and rare earths from the electrode materials of spent nickel metal-hydride(Ni-MH) secondary battery. MmNis_xCo. (Mm : Misch metal) intermetallic compound could be separated from the electrode materials mixture by sedimentation. A typical chemical composition of MmN5-xCox was approximately, in mass%, 56.0%Ni, 13.4%Ce, 10.6%La and 7.9%Co. The time dependency of leaching intermetallic compound with sulfuric acid solution was examined with processing factors such as sulfuric acid concentration, temperature and agitation intensity, The leaching of rare earth metals proceeded very rapidly, reaching completion in less than 1.8ks. On the other hand, the slow leaching of nickel was observed. The percent of nickel leached at 328K could only reach about 70%.